Mining noise data for monitoring Arctic permafrost by using GNSS interferometric reflectometry - Zhang, Jiahua; Liu, Lin (Polar Science, 2021)
Ground surface elevation changes are closely linked to the dynamics of the active layer and near-surface permafrost. GNSS interferometric reflectometry (GNSS-IR), a technique utilizing reflected signals regarded as noise in the GNSS applications, such as positioning and navigation, can measure surface elevation changes in permafrost areas. In this study, we screen seven major open-data GNSS networks to identify the sites which are suitable for using GNSS-IR to study the permafrost areas in the Arctic. We identify 23 usable sites and obtain their surface elevation changes. As for the unusable sites in the permafrost areas, 68% and 25% of them are due to undulated reflecting surface and obstructions (e.g., buildings and trees), respectively. And 7% of the unsuitable sites are due to insufficient usable observations, though open and relatively smooth areas can be found in their surroundings. This study provides usable sites in the Arctic permafrost areas, which can fill some spatial gaps of the existing permafrost monitoring programs and provide complementary measurements to active layer thickness and permafrost temperature. The GNSS-IR measurements can provide new perspectives into permafrost studies and contribute to assessing the potential hazards of permafrost degradation to infrastructures and residential communities. journal article